Biomarkers and possible mechanisms of operational tolerance in kidney transplant patients. Issue 1 (March 2014) - Dugast, Emilie; Chesneau, Mélanie; Soulillou, Jean‐Paul; Brouard, Sophie
Summary: A small number of patients do not reject their graft after weaning from immunosuppressive treatment. Here, we analyze the studies carried out to try to understand the mechanisms involved in this operational transplant tolerance and evaluate the hypotheses proffered on these potential mechanisms.